A study on sustainability assessment of welding processes. (February 2020) - Jamal, Jaber; Darras, Basil; Kishawy, Hossam
The concept of "sustainability" has recently risen to take the old concept of going "green" further. This article presents general methodologies for sustainability assessments. These were then adapted to measure and assess the sustainability of welding processes through building a complete framework, to determine the best welding process for a particular application. To apply this methodology, data about the welding processes would be collected and segregated into four categories: environmental impact, economic impact, social impact, and physical performance. The performance of each category would then be aggregated into a single sustainability score. To demonstrate the capability of this methodology, case studies of three different welding processes were performed. Friction stir welding obtained the highest overall sustainability score compared to gas tungsten arc welding and gas metal arc welding.